2000
DOI: 10.1074/jbc.m001857200
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Endothelial Cell Adhesion Molecule-1 (CD31), a Scaffolding Molecule for Selected Catenin Family Members Whose Binding Is Mediated by Different Tyrosine and Serine/Threonine Phosphorylation

Abstract: Platelet-endothelial cell adhesion molecule (PE-CAM)-1 is a 130-kDa glycoprotein commonly used as an endothelium-specific marker. Evidence to date suggests that PECAM-1 is more than just an endothelial cell marker but is intimately involved in signal transduction pathways. This is mediated in part by phosphorylation of specific tyrosine residues within the ITAM domain of PECAM-1 and by recruitment of adapter and signaling molecules. Recently we demonstrated that PECAM-1/␤-catenin association functions to regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 48 publications
(39 reference statements)
8
100
0
Order By: Relevance
“…An ITAM (immunoreceptor tyrosine-based activation motif) domain, encoded by exons 12, 13, and 14, has been identified in the cytoplasmic tail of PECAM-1 (19). PECAM-1 has been noted to be phosphorylated by fluid flow and osmotic shock and also to associate with adapter and signaling molecules in an ITAM-independent manner, as was recently shown for ␤-catenin (20), ␥-catenin (21), and STAT (signal transducers and activators of transcription) (22) family members. Functionally, PECAM-1 tyrosine phosphorylation has been shown to play a role in endothelial cell migration and angiogenesis (23,24).…”
Section: Vascular Endothelial Cells (Ecs)mentioning
confidence: 85%
“…An ITAM (immunoreceptor tyrosine-based activation motif) domain, encoded by exons 12, 13, and 14, has been identified in the cytoplasmic tail of PECAM-1 (19). PECAM-1 has been noted to be phosphorylated by fluid flow and osmotic shock and also to associate with adapter and signaling molecules in an ITAM-independent manner, as was recently shown for ␤-catenin (20), ␥-catenin (21), and STAT (signal transducers and activators of transcription) (22) family members. Functionally, PECAM-1 tyrosine phosphorylation has been shown to play a role in endothelial cell migration and angiogenesis (23,24).…”
Section: Vascular Endothelial Cells (Ecs)mentioning
confidence: 85%
“…Syndecans that contain both HS and CS have an established association with the cytoskeleton [19], and through it can decentralize the signal by distributing it to multiple sites within the cell (i.e., nucleus, organelles, focal adhesions, intercellular junctions). Significantly, the platelet-endothelial cell adhesion molecule (PECAM-1) associates with the cytoskeleton through catenins, and has been linked to shearinduced eNOS activation [20][21][22]. In terms of central transduction, it is noteworthy that glypicans which contain HS, but not CS, are linked to caveolae where eNOS resides along with many other signaling molecules [3].…”
Section: Discussionmentioning
confidence: 99%
“…For example, during thrombin-induced platelet aggregation, PECAM-1 partitions with the Triton-insoluble cytoskeleton increased from 10% to 60% of total cellular PECAM-1 [33]. In confluent endothelial cells, 20% to 30% of PECAM-1 was found associated with the cytoskeleton [31,34] and it increased to 65% during cell migration [31].…”
Section: Discussionmentioning
confidence: 99%
“…A functional relationship between PECAM-1 and the cytoskeleton is being recognized as growing evidence has showed that PE-CAM-1 associates both physically and functionally with the underlying cytoskeleton [30,31]. It has been reported that the reorganization of actin cytoskeleton (stress fiber formation), and redistribution of a group of endothelial cell tight junction proteins from the TX-100-soluble to the TX-100-insoluble fractions are associated with transendothelial permeability in brain endothelial cells [32].…”
Section: Discussionmentioning
confidence: 99%